The Relationship of Parental Participation in Learning with Student Achievement on Biology Subjects - Syahrul Alam; Armin Sinaga (Lembaga Intelektual Muda Maluku, 2024)
Parental participation is a factor that plays a very important role. This is inseparable from the fact that parental participation plays a role in the formation of student attitudes and achievement. This study aims to determine the relationship between parental participation and the learning achievement of Science-Biology grade VII students at SMP Negeri 4 Medan. The type of research used is correlational. The number of samples used was 29 people taken using cluster random sampling. The instruments used are tests and questionnaires. Tests are used to determine student achievement through report card scores and questionnaires are used to determine parental participation in student learning. The data analysis used is Product Moment Correlation analysis. The results showed that there was a strong relationship between parental participation and the achievement of science-biology learning of grade VII students at SMP Negeri 4 Medan with a large influence of 59.31%, and 40.69% influenced by other factors.